2020
DOI: 10.35808/ijeba/554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transformational Leadership and Breakthrough Leadership on Organizational Performance through the Variable of Employee Satisfaction: A Case Study

Abstract: Purpose: The article investigates the impact of transformational leadership and breakthrough leadership on organizational performance both directly and through intervening variables. Design/ Methodology/Approach: This type of research is a quantitative method. Primary data were obtained from questionnaires distributed while secondary data were obtained from a company's annual reports published. Respondents are employees of 15 coal mining companies listed in Indonesia stock exchange with a total of 201 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Managerial and strategic planning implication is paramount in developing and maintaining an organization's good performance through increased employee satisfaction. Furthermore, the management and strategic planning elements work in tandem with information-sharing capabilities and effective information flow in generating a favorable organizational environment, which is critical in managing VUCA in the market setting (Triraharjo et al, 2020) (Rose et al, 2019). Kryvoruchko et al (2018) suggested in their study on enterprise management in a VUCA environment that SMEs must be more dynamic in their entrepreneurial management and more agile in adjusting their business models to remain relevant to evolving customer trends that have become more sophisticated in recent years.…”
Section: Organization Performance Factors Inmentioning
confidence: 99%
“…Managerial and strategic planning implication is paramount in developing and maintaining an organization's good performance through increased employee satisfaction. Furthermore, the management and strategic planning elements work in tandem with information-sharing capabilities and effective information flow in generating a favorable organizational environment, which is critical in managing VUCA in the market setting (Triraharjo et al, 2020) (Rose et al, 2019). Kryvoruchko et al (2018) suggested in their study on enterprise management in a VUCA environment that SMEs must be more dynamic in their entrepreneurial management and more agile in adjusting their business models to remain relevant to evolving customer trends that have become more sophisticated in recent years.…”
Section: Organization Performance Factors Inmentioning
confidence: 99%